PENERAPAN BLENDED LEARNING TERHADAP PERSEPSI DAN KEPUASAN SISWA DITINJAU BERDASARKAN GENDER - Annisa Rahmadani; Kurjono Kurjono; Hari Mulyadi (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2022)
This research aims to find out how students' perceptions and satisfaction with the application of Blended Learning in the Social Studies Department at Madrasah Aliyah Negeri (MAN) 1 and Madrasah Aliyah Negeri (MAN) 2 Pekanbaru model based on gender. This type of research is Quantitative Research. Proportional Stratified Random Sampling technique was used to take samples in this study. The data used are 114 respondents from students of MAN 1 Pekanbaru and 50 respondents from students of MAN 2 Pekanbaru Model. This research method uses quantitative descriptive analysis. The data used are interviews and questionnaires. Validity Test and Reliability Test were used before the research instrument was distributed to the respondents. Data Analysis Techniques using t test. The results of the Perception and Satisfaction research of students are positively and significantly influenced by the application of Blended Learning to students of MAN 1 and MAN 2 Pekanbaru Model, and there is a significant difference between Perception and Satisfaction of Students and Students. Satisfaction with the implementation of BL in MAN 1 Pekanbaru and MAN 2 Pekanbaru model by utilizing the CSI calculation, it can be seen that satisfaction with the implementation of BL shows the category of being satisfied with the range of 66-80% and quite satisfied which is in the range of 51%-65%.